Education Quality Management of Midwife Clinical Laboratory in Improving Graduates' Competence - Rukiyah, Ai Yeyeh; Wasliman, Iim; Sauri, Supyan (Tahta Media Group, 2022)
Higher Education has the function of developing capabilities in order to educate the nation's life in accordance with Law Number 12 of 2012 concerning Higher Education. The aim of this research is to analyze and describe in depth through a field study of the quality manajement of midwifery clinical laboratories in increasing the competence of graduates (case studies of midwifery practice at Polytechnic Bhakti Asih Purwakarta and Stikes Kharisma Karawang. The research method in this dissertation used a qualitative approach. Data were collected using in-depth interviews, observation, and documentation study. The data of this study were checked for correctness and reliability through the triangulation process. Based on the results of the research, the implementation process of the midwifery clinical laboratory practice learning at the Bhakti Asih Polytechnic of Purwakarta and Stikes Kharisma Karawang went well. The method taught to students when conducting laboratory practice simulations makes a positive contribution to student competence and graduate competence. Weak points that arise in the implementation of learning are limitations in the infrastructure and facilities in each institution, and practice supervisors are still lacking in clinical experience in the field so that manajement has an impact on the quality of midwifery clinical laboratory manajement.